Other People’s Myths: Interpretation and Difference - Inder, John (The international journal of religion and spirituality in society, 2017)
Wishing to deepen in understanding of myths from other cultures, the author seeks to first learn about interpretation from the history of biblical hermeneutics up to the mid-nineteenth century. This requires a separation of myth from other elements found in the Holy Scriptures. With that as a base, consideration is given to more recent thinking on hermeneutics by Gadamer and other post-romantic theorists. The search for meaning in myth then moves through considerations of the intentions of authors, the universality of mythic characters, hearer/actor/reader reception, and otherness itself. The special status of myth as opposed to other textual forms of discourse is highlighted. An informed look at the myths of another tradition will reveal inter-religious and inter-cultural differences that should not be minimized. Exposure to the myths of other peoples can permit increased self-knowledge as well as knowledge of other cultures. It will be argued that meaning in myth is open for all to discover and that even the cultures that preserved these traditions cannot claim to have a definitive understanding. One implication that arises from the chronological presentation of hermeneutic approaches is that, contra Gadamer, the "hermeneutic method" itself is an example of progress in the historical sciences.